An Easy And Reliable Method For Syringyl: Guaiacyl Ratio Measurement - Raquel Prado; Lisa Weigand; S. M.S.N.S. Zahari; Xabier Erdocia; Jason P. Hallett; Jalel Labidi; Tom Welton (Technical Association of the Pulp and Paper Industry Inc., 2024)
Indexed by SCOPUS